Предмет: Алгебра, автор: darlunova488

Упростите выражения: а) 4х^4*(-2х^2)^3; б)(3х-1)(3х+1)+(3х+1)^2. Разложите на множители: а)25а-аb^2; б)3а^2-6а+3.

Ответы

Автор ответа: maymr
1

а)

4x⁴ * (-2x²)³ = 4x⁴ * (-8x⁶) = -32x¹⁰

б)

(3x - 1)(3x + 1) - (3x + 1)² = 9x² - 1 + (9x² + 6x + 1) = 9x² - 1 + 9x² + 6x + 1 = 18x² + 6x

_______________________

а) 25a - ab² = a(25 - b²) = a(5 - b)(5 + b)

б) 3a² - 6a + 3 = 3(a² - 2a + 1) = 3(a - 1)(a - 1) = 3(a - 1)²

Похожие вопросы
Предмет: Математика, автор: Ksushats77